An issue on uniform customs and practice for documentary credits (UCP) no 600 for Islamic letter of credit - Syed Alwi, Sharifah Faigah; Ibrahim, Uzaimah; Sawari, Fuad (ELSEVIER, 2013)
Islamic banks in Malaysia offer Letter of Credit (LC) Wakalah (agency) and LC Murabahah (cost-plus) as two of their main trade finance facilities. LC is the product of International Chamber of Commerce, the world business organization based in Paris and it is governed by the Uniform Customs and Practice for Documentary Credits (UCP) No. 600 (UCP 600). The objective of this paper is to clarify an issue on a few articles of the UCP 600 as the governing rules of LC Wakalah and LC Murabahah. At the same time, this paper discusses the practice of some Islamic banks in Malaysia in facing this issue. This study adopts the qualitative method as the main research methodology where both the primary and the secondary data are used. For the primary data, semi-structured interviews were conducted with bankers who are directly involved with the operation of Islamic LCs. As the result, this paper discovers an issue on the UCP 600 for Islamic LCs that is the issue of insufficiency in dealing solely with documents for LC Wakalah and LC Murabahah without checking the conditions of goods. This paper analyzes this issue by determining whether it is in line with the Shariah principles. Lastly, a solution to resolve the issue on the UCP 600 for Islamic LCs is recommended to Bank Negara Malaysia.